Alternate Land Use Systems in Rainfed Areas - Venkateswarlu, J (Annals of Arid Zone, 2016)
Rainfed agriculture in India is now facing a dilemma. Prime lands for rainfed agriculture, which are mostly with big farmers, are being gradually taken out of food crop cultivation for commercial cropping and even non-arable systems. On the other hand, demand for food and oilseed crops are increasing due to rise in population. A large part of the available land with resource-poor farmers can ill-afford improved technologies higher demands mean cultivation of less suitable lands with lesser returns and greater risk of land degradation. To tackle tile problem land users, at various levels, are to be made aware of tile proper use of their land resources. Providing the alternative for sustainable land uses should follow proper evaluation of the land resources. The land users are to be encouraged to participate in tile whole exercise of land inventorization and evolution of an action plait for proper use of their lands.